The association among health behaviors, shift work and chronic morbidity: A cross-sectional study on nurses working in full-time positions - Dominika Berent; Mariusz Skoneczny; Marian Macander; Marcin Wojnar (SAGE Publishing, 2021)
Background: Nurses are known to work in conditions of stress and physical overload. Health behaviors are modifiable factors that may reduce the adverse effects of work on general health. The present study examined health-related behaviors and their association with current night shift work and chronic morbidity among female nurses. Design and Method: Four hundred seventy-two female nurses (M ± SD = 44.28±7.14 years) self-reported their health habits, physical activity, body mass index (BMI), and chronic disorders that required current treatment. Instruments used in the study consisted of an author-developed questionnaire and the Health Behavior Inventory (HBI). Reported diagnoses were classified as cardio-vascular, gastro-intestinal, malignant neoplastic, endocrine, or other. Results: The most common reported disorders were cardiovascular disorders (5.7% of nurses) followed by other (7.6%), endocrine (7.4%), gastro-intestinal (6.4%), and malignancy (0.2%). On average, health-related behaviors on the HBI were average (83.49 ± 14.33). Overweight and/or obesity (i.e., BMI ≥ 25 kg/m2) were reported by 41.5% of nurses, 24.2% were current smokers, and 36% reported no recreational physical activity. The remaining 64% of nurses who performed physical activity did not report activity levels that met World Health Organization recommendations. Physical activity and HBI scores (total and subscales; i.e., positive attitude, preventive behaviors, proper dietary habits, health-related practices) were not associated with current night shift work or morbidity. Conclusion: Health-promoting programs are needed to support weight control and promote health-related behaviors among nurses. Future research should identify potential barriers to healthy lifestyle recommendations in the workplace.